Assessing the Biological Markers of MiRNA-9 and 192 Expression Levels in Cervical Cancer - Tavakolian, Shaian; Atani, Zahra Rafiei; Faghihloo, Ebrahim (Advanced biomedical research, 2025)
Background: Various risk factors thought to impact cervical cancer progression. One way these factors influence cancer development is through changes in the microRNA's expression, which are small, non-coding, single-stranded RNA molecules around 20-23 nucleotides long. In cervical cancer, specific miRNAs, notably miRNA-9 and miRNA-192, are gaining attention as potential clinical biomarkers. Materials and Methods: RNA was extracted from cervical intraepithelial neoplasia grade I, II, and III (CIN I, CIN II, and CIN III) tissues, as well as their adjacent normal tissues, to compare the expression levels of miRNA-9 and miRNA-192 as potential biomarkers. The extracted RNAs were then converted to cDNA for evaluation using quantitative PCR (qPCR). Results: Pathological analysis revealed that 80% of patients with cervical cancer and CIN III tissues were diagnosed with squamous cell carcinoma, while the proportions for adenocarcinoma and adenosquamous cell carcinoma were 13.4% and 6.6%, respectively. Our data indicated a significant increase in the expression of miRNA-192-5p (P < 0.05) in 15 cervical cancer and CIN III tissues compared to CIN I and CIN II. Similarly, miRNA-9 expression was also elevated in cervical cancer and CIN III tissues relative to CIN I and CIN II. Conclusions: miRNA-9 and miRNA-192 may serve as promising biomarkers for cervical cancer, given their elevated expression levels in the both cervical cancer and CIN III tissues. This expression pattern implies that they could aid in detecting early stages of cervical cancer progression, potentially improving early diagnosis and monitoring. However, further studies are essential to confirm these preliminary findings and validate their clinical relevance.